Interventions and implementation considerations for reducing pre-treatment loss to follow-up in adults with pulmonary tuberculosis: A scoping review [version 1; peer review: 2 approved] - Eleanor Ochodo; Eddy Johnson Owino; Mercy Mulaku; Taryn Young (F1000Research)
Background Tuberculosis (TB) is a leading cause of death worldwide with over 90% of reported cases occurring in low- and middle-income countries (LMICs). Pre-treatment loss to follow-up (PTLFU) is a key contributor to TB mortality and infection transmission. Objectives We performed a scoping review to map available evidence on interventions to reduce PTLFU in adults with pulmonary TB, identify gaps in existing knowledge, and develop a conceptual framework to guide intervention implementation. Methods We searched eight electronic databases up to February 6 2024, medRxiv for pre-prints, and reference lists of included studies. Two review authors independently selected studies and extracted data using a predesigned form. We analysed data descriptively, presented findings in a narrative summary and developed a conceptual framework based on the Practical, Robust Implementation, and Sustainability Model to map the factors for effective intervention implementation. Results We reviewed 1262 records and included 17 studies. Most studies were randomized controlled trials (8/17, 47%). Intervention barriers included stigma and inadequate resources; enablers included mobile phones and TB testing and results on the same day. We identified eight interventions that reduced PTLFU: treatment support groups; mobile notifications; community health workers; integrated HIV/TB services; Xpert MTB/RIF as the initial diagnostic test; computer-aided detection with chest radiography screening; active linkage to care; and multi-component strategies. Conclusion Given the variation of healthcare settings, TB programs should consider contextual factors such as user acceptability, political commitment, resources, and infrastructure before adopting an intervention. Future research should utilize qualitative study designs, be people-centred, and include social and economic factors affecting PTLFU.